2016
DOI: 10.1097/md.0000000000004934
|View full text |Cite
|
Sign up to set email alerts
|

Well-differentiated systemic mastocytosis showed excellent clinical response to imatinib in the absence of known molecular genetic abnormalities

Abstract: Introduction:Well-differentiated systemic mastocytosis (WDSM) is a rare, recently recognized provisional subvariant of systemic mastocytosis (SM). We report a case of WDSM that showed excellent clinical and cutaneous response to imatinib in the absence of known molecular genetic abnormalities.Clinical Findings/Diagnoses:We present a 24-year-old woman with childhood onset of skin manifestations that progressed to mediator-related systemic events, and a gastrointestinal tract mastocytoma. A subsequent bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In addition, one study revealed that approximately 20% of ISM patients lack mast cell clusters in the bone marrow, and ~30% of ISM patients show a serum tryptase level below 20 ng/mL [ 30 ]. Of note, serum tryptase levels are correlated with mast cell activation of all the mast cells in various organs and do not solely reflect neoplastic mast cell activity [ 31 ]. Furthermore, normal mast cells demonstrate a range of activation, and the biology of the secretory phenotype and mediator release patterns have not been fully elucidated [ 32 ].…”
Section: Updates In Diagnosis and Subclassification Of Systemic Masto...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, one study revealed that approximately 20% of ISM patients lack mast cell clusters in the bone marrow, and ~30% of ISM patients show a serum tryptase level below 20 ng/mL [ 30 ]. Of note, serum tryptase levels are correlated with mast cell activation of all the mast cells in various organs and do not solely reflect neoplastic mast cell activity [ 31 ]. Furthermore, normal mast cells demonstrate a range of activation, and the biology of the secretory phenotype and mediator release patterns have not been fully elucidated [ 32 ].…”
Section: Updates In Diagnosis and Subclassification Of Systemic Masto...mentioning
confidence: 99%
“…A limited number of WDSM cases have been reported to date [ 28 , 31 , 36 , 38 , 39 , 40 , 41 , 42 , 43 ]. Clinically, WDSM has an early onset presentation with familial aggregation, female predominance, and cutaneous involvement.…”
Section: Updates In Diagnosis and Subclassification Of Systemic Masto...mentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, mast cells in WDSM are less likely to have KIT mutations, are often morphologically normal (round), and do not show aberrant expression of CD2 and CD25; thus, they often do not fulfill the WHO criteria for SM. However, establishing the diagnosis of WDSM is important because this form of SM is often responsive to imatinib, 113 and thus alternative diagnostic criteria were proposed. 17 Clinical criteria for suspecting WDSM are not fully established, but they include persistence of skin disease, female sex, and familial mastocytosis.…”
Section: Bone Marrowmentioning
confidence: 99%
“…Wild-type KIT can be currently targeted by a progressively higher number of small tyrosine-kinase inhibitor (TKI) molecules including some that—e.g., midostaurin (PKC412) or imatinib—have proven beneficial for SM [10,11,12,13]. However, overall CR rates, even with these new drugs still remain low, except among the few WDSM patients presenting with mutations at exons 9 and 10 of KIT [14,15,16,17,18]. Altogether, this highlights the need for further improvement in the treatment of SM, particularly for advanced SM [19].…”
Section: Introductionmentioning
confidence: 99%